Potential favorable action of sodium-glucose cotransporter-2 inhibitors on sudden cardiac death: a brief overview - Sato, Tatsuya; Kouzu, Hidemichi; Yano, Toshiyuki; Sakuma, Ichiro; Furuhashi, Masato; Tohse, Noritsugu (Frontiers in Cardiovascular Medicine, 2023)
The primary pharmacological action of sodium-glucose co-transporter 2 (SGLT2) inhibitors is to inhibit the reabsorption of glucose and sodium ions from the proximal tubules of the kidney and to promote urinary glucose excretion. Notably, several clinical trials have recently demonstrated potent protective effects of SGLT2 inhibitors in patients with heart failure (HF) or chronic kidney disease (CKD), regardless of the presence or absence of diabetes. However, the impact of SGLT2 inhibitors on sudden cardiac death (SCD) or fatal ventricular arrhythmias (VAs), the pathophysiology of which is partly similar to that of HF and CKD, remains undetermined. The cardiorenal protective effects of SGLT2 inhibitors have been reported to include hemodynamic improvement, reverse remodeling of the failing heart, amelioration of sympathetic hyperactivity, correction of anemia and impaired iron metabolism, antioxidative effects, correction of serum electrolyte abnormalities, and antifibrotic effects, which may lead to prevent SCD and/or VAs. Recently, as possible direct cardiac effects of SGLT2 inhibitors, not only inhibition of Na+/H+ exchanger (NHE) activity, but also suppression of late Na+ current have been focused on. In addition to the indirect cardioprotective mechanisms of SGLT2 inhibitors, suppression of aberrantly increased late Na+ current may contribute to preventing SCD and/or VAs via restoration of the prolonged repolarization phase in the failing heart. This review summarizes the results of previous clinical trials of SGLT2 inhibitors for prevention of SCD, their impact on the indices of electrocardiogram, and the possible molecular mechanisms of their anti-arrhythmic effects.